Conceptual demonstration of martian atmosphere-breathing electrical supersonic thruster with CO2-based rotating gliding arc. (November 2022) - Kang, Hongjae; Lee, Jeongrak; Kim, Kwan-Tae; Song, Young-Hoon; Lee, Dae Hoon
Abstract: Martian atmosphere-breathing propulsion systems are essential for a near-Mars satellite infrastructure. The present research is to explore a novel concept of Martian atmosphere-breathing electrical supersonic arc thruster. Rotating gliding arc is discharged with CO2 gas to simulate the compositions of Martial atmosphere. The operating pressure in the discharge chamber is almost three times higher than the atmospheric pressure at sea level on Earth. The pressurized plasma gas is accelerated to supersonic flow with the converging and diverging nozzle. The definition of the specific energy input can be utilized as a design element for the thruster. The minimum criterion of the specific energy input is approximately 5.6 kJ/L for the stable operation. Highlights: Martian atmosphere-breathing electrical supersonic arc thruster is demonstrated. CO2 -based rotating gliding arc is used as a thermal plasma source. The operating pressure in the discharge chamber is higher than the atmospheric pressure at the sea-level on Earth. The pressurized CO2 plasma gas can be accelerated to supersonic flow.